Validitas Modul Kimia Berbasis Problem Based Research PBR pada Materi Larutan Elektrolit dan Nonelektrolit - Citra Ayu Dewi; Teti Fitri Handayani (IKIP Mataram, 2015)
The purpose of this study was to determine the validity of the module based on Problem Based Research (PBR) on electrolyte and non-electrolyte solution material. This research is a descriptive qualitative research to assess and obtain chemical modules on electrolyte solution and non-electrolyte material based on Problem Based Research (PBR). Module development in this study follows the three stages of the ADDIE model, namely, the analysis stage (Analyze), the design stage (Design), and the development stage (Development). Data obtained using questionnaires. The results of the expert lecturer validation showed that the module is valid with a percentage of 81.5%. The results of the expert validity test showed a validity percentage of 92.5%. Furthermore, the group trial was limited to 10 students, the responses were obtained that the aspects of language, readability, and appearance of the module were very good. These results indicate that the Problem Based Research (PBR) -based module on electrolyte and non-electrolyte solution material is developed valid to be continued at the implementation stage, and evaluation.